INCIDENCE OF COLON NEOPLASIA CASES IN THE NORTHEAST REGION DURING THE COVID-19 PANDEMIC - Eduarda Almeida de Souza, Cicera; Mohamad Abdel Salam Suleiman, Nariman; Costa Silva, Karoline; Wágner Holanda Lima, Mariel; Luís Sotério Lima, Leandro; da Costa Araújo, Paulo; Well do Amaral Rêgo, Pablo; Beatriz Araujo Duarte, Ana; Santos Araújo, Malanny; Costa Duarte, Tamires (Health and Society, 2023)
Introduction: Cases of colon cancer is a very common condition and it is a tumor that originates in the colon, also called colon and rectum cancer. It is a preventable disease because it most often arises from polyps, which are benign lesions that develop on the intestinal wall. Removing polyps prevents them from becoming cancerous. Therefore, knowing the progression in which neoplasms are evolving, this research is justified by its academic, scientific and social relevance, with a view to presenting data related to colon cancer. Objective: To analyze the epidemiological index of colon cancer in the northeast region, before and during the pandemic. Methodology: This study was carried out through a cross-sectional analysis, whose purpose was the collection and interpretation of data that cover the epidemiological data of reported cases of neoplasia in the northeast region during the Covid-19 pandemic. Data collection took place between May and December 2022, using the Notifiable Disease Information System - SINAN and the Unified Health System Database - DATASUS, where the collected data are concentrated between September 2018 and August 2021 referring to the states of the northeast region of Brazil. Results and Discussion: Regarding the analysis process carried out in Graph 2, the findings indicate that there was a greater increase than the period before the pandemic. In addition, the year-over-year increases were greater, due to several factors pointed out in the literature. With the peak stages of Covid-19, health services were focused on tracking, diagnosing, preventing and controlling the coronavirus, to a certain extent, neglecting less urgent occurrences in health services. In the period during the pandemic, it can be seen that the states in the northeast region continue to lead the incidence of notifications. Thus, it is worth mentioning, more specifically, that Bahia and Ceará continue to stand out among the states with the highest incidence, with the state of Pernambuco also standing out, which emerged with a growing increase in notification rates. Conclusion: The course of this research had the general objective of analyzing the epidemiological index of colon cancer in the northeast region, before and during the pandemic. Priority was given to this field of investigation, due to the fact that there are difficulties and gaps in knowledge about notification rates. This outlined objective was achieved, allowing to demonstrate that the data show an increasing increase year after year.